Distribution and Abundance of Microplastics in Underground Rivers in the South Malang Karst Area: First Evidence in Indonesia - Suprayogi, Dedy; Utama, Teguh Taruna; Hadi, Moch Irfan; Agung, Tri Sunan; Rizqiyah, Ziadatur (JURNAL KESEHATAN LINGKUNGAN, 2024)
Introduction: The presence of microplastics in the environment increases the diversity of types of pollutants in waters, including clean water sources on the surface and underground. Karst areas have unique hydrological characteristics, with cracks and fissures between the rocks that can be potential routes for the transport and accumulation of microplastics in underground river flows. In this study, we want to know the distribution and abundance of microplastics in underground rivers in the karst area of South Malang, Indonesia. Methods: Samples were collected purposively from underground river of Lowo, Banyu and Sengik. Microplastics were prepared using a diluted solvent of 30% H2SO4 and 30% H2O2. The sediment sample was dried and then filtered twice using 300-mesh size nylon filters until microplastic particles accumulated. Results and Discussion: Microplastics were detected in all water samples, with an average abundance ranging from 1.8 to 2.3 particles per liter. Fibers were the dominant microplastic type, followed by fragments and films, while the color distribution includes blue, white, red, yellow, black, green, pink, and brown. Conclusion: Microplastic contamination has been found in underground river flows in the karst area of South Malang, Indonesia. Karst soil, traditionally viewed as a natural filter, is not impervious to plastic pollution. This suggests significantly higher surface contamination than previously assumed. Therefore, reducing surface pollution is essential to safeguard the precious quality of underground aquifers and protect public health above.